INVESTMENT IS THE HEART OF THE ECONOMY (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
According to paragraph 60 of the minutes of the meeting No. 30 of the President of the Republic of Uzbekistan during his visit to the Surkhandarya region on June 1-2, 2021 and the decision "On confirmation of the administrative regulation for selecting the best proposal for the implementation of a large investment project" It is planned to establish a "Trade and Production Complex" by "Angor Index" LLC in the "Tallimaron" massif near the M39 highway, Angor district.